Role of salivary transcriptomics as potential biomarkers in oral cancer: A systematic review. (25th June 2019) - Patil, Shankargouda; Arakeri, Gururaj; Alamir, Abdul Wahab H.; Awan, Kamran Habib; Baeshen, Hosam; Ferrari, Marco; Patil, Shekar; Fonseca, Felipe Paiva; Brennan, Peter A.
Abstract: Introduction: Transcriptomes in saliva can be used as potential biomarkers for both diagnostic and response to treatment in oral squamous cell carcinoma (OSCC). In this review, we explored their application in this increasingly common disease. Materials and methods: PubMed, EMBASE, Scopus, Web of Science and grey literature from January 1990 to May 2017 were searched. Two independent reviewers performed the study selection according to eligibility criteria. Results: A total of nine studies were included. Three studies showed increased expression of DUSP1, IL8, IL1B, OAZ1, SAT1, S100P and two showed increased expression of miRNA‐31 among study groups compared to normal healthy controls. The sensitivity ranged from 14% to 100%, while the specificity ranged from 38% to 100%. miRNA‐27b had the highest AUC (write in full) of 0.9643 and DUSP1 had the minimum AUC of 0.41. Conclusion: Salivary transcriptomics may play an effective role as a robust and non‐invasive biomarker sighting tool for the diagnosis and management of OSCC.